Udział poleis Grecji egejskiej w rzymskich wojnach w I w. p.n.e - Pawlak, Marcin (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
The article shows which poleis of the Aegean Greece took part in the wars waged by Rome in the 1st century B.C. and explains why Roman leaders sought their help.
Keywords: Grecja egejska w I w. p.n.e; rzymskie wojny domowe